Lack of residual morning effects of lemborexant treatment for insomnia: summary of findings across 9 clinical trials. Issue 1 (2nd January 2021) - Moline, Margaret; Zammit, Gary; Yardley, Jane; Pinner, Kate; Kumar, Dinesh; Perdomo, Carlos; Cheng, Jocelyn Y.
ABSTRACT: Objectives: Residual next-day effects of sleep-promoting drugs are common and an important safety issue. Lemborexant is a dual orexin receptor antagonist approved in the United States and Japan for treatment of insomnia in adults. We evaluated the potential of lemborexant for residual morning and next-day effects, including somnolence, based on lemborexant clinical study findings. Methods: This paper reports findings from 9 lemborexant clinical studies that incorporated next-day assessments of residual drug effects, based on published findings and data on file. Results are reported for healthy subjects or subjects with insomnia disorder treated with lemborexant 5 mg/day or 10 mg/day, placebo, or active comparator before bedtime. Outcomes assessed included next-morning postural stability (body sway measured by ataxiameter), cognitive performance (Cognitive Performance Assessment Battery), impact on driving (standard deviation of lateral position during highway driving test), subjective sleepiness (sleep diary entries), and adverse events of somnolence. Results: Change from baseline in postural stability the morning after lemborexant administration did not differ from placebo. Among 4 Cognitive Performance Assessment Battery measures, only power of attention declined significantly more with lemborexant treatment compared with placebo in 1 of 2 studies, whereas zolpidem differed from placebo on multiple measures. On the highway-driving test, lemborexant did not significantly impair driving performance versus placebo, however, zopiclone did differ. In large phase 3 trials, next-morning sleep diary ratings showed significantly greater alertness with lemborexant compared with placebo after up to 6 months of treatment. As expected, somnolence was the most common adverse event reported with lemborexant treatment. Somnolence was typically mild to moderate in severity and rarely caused discontinuation of study drug. Conclusion: Across 9 clinical studies, lemborexant did not substantially impair next-day functioning among healthy subjects and subjects with insomnia.